Combined use of salivary biomarkers and carcinoembryonic antigen for lung cancer detection in a Chinese population. Issue 31 (August 2019) - Shang, Xi; Zi, Huanpu; Li, Yangyang; Gao, Yu; Ge, Changsheng; Sun, Zhongmei; Zhang, Youmin
Abstract : Abstract: Blood-based biomarkers, such as carcinoembryonic antigen (CEA), and saliva-based biomarkers, such as mRNA, have emerged as potential liquid biopsies for non-invasive detection of many cancers. However, current tests typically use single type of biomarkers, and their sensitivity and specificity is often unsatisfactory. In this study, we developed a novel biomarker panel that measures both CEA level in blood and GREB1 and FRS2 levels in saliva to achieve high sensitivity and high specificity in detecting Non-Small Cell Lung Cancer (NSCLC). In the discovery phase, we achieved sensitivity of 96.67% and specificity of 93.33% for 30 NSCLC patients and 30 healthy controls. To further evaluate the prediction performance of our biomarker panel, we applied it to an independent set of 15 NSCLC cancer patients and 25 healthy controls. The sensitivity and specificity of our test reached 93.33% and 80.00% respectively. Our study discovered that the combined analysis of CEA and mRNA can be a novel liquid-biopsy technology for non-invasive detection of NSCLC.